Peripherals Using in Working Area - Antara, Gede Krisnanda Juni (International Research Journal of Management, IT & Social Sciences, 2015)
Peripherals is additional hardware who connected to the computer, usually with the aid of wires or now many wireless peripheral devices. These computer peripherals duty to help accomplish the task cannot be performed by hardware which is mounted inside the casing. These peripherals can be divided into 2 of the input and output peripherals. In daily activities, peripherals much help humanity though not much like the example Printer. Human previously prints using a typewriter that is very inefficient and after the invention of a machine that can print very fast then this machine that replaces the role of the previous cumbersome machine becomes very easy to use. In its development until now very much changed peripherals ranging in terms of composition and form very striking. For example a mouse which only consists of 1 buttons until now that could be a wireless